2003
DOI: 10.1016/s1470-0328(02)02390-x
|View full text |Cite
|
Sign up to set email alerts
|

Choices about abortion method: assessing the quality of patient information leaflets in England and Wales

Abstract: Objective To assess the quality of patient leaflets regarding the choice between medical and surgical abortions.Design Cross sectional survey.Setting NHS and private providers of abortion services in England and Wales.Sample Leaflets from three private providers, all teaching hospitals (n ¼ 14) and a representative sample of NHS district hospitals (n ¼ 27), accessed by approximately 100,000 women per year. Methods On telephoning the above abortion services, the leaflets provided to women choosing to have medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This proportion is higher than the 11% of women in the Danish trial, who expressed no preferences and were willing to be randomized to receive either treatment [7]. Insufficient or poor quality information may be a barrier to achieve greater patient autonomy [14], but changes in the approach to clinician-patient partnerships may also take time to fully be integrated in the French health care system.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is higher than the 11% of women in the Danish trial, who expressed no preferences and were willing to be randomized to receive either treatment [7]. Insufficient or poor quality information may be a barrier to achieve greater patient autonomy [14], but changes in the approach to clinician-patient partnerships may also take time to fully be integrated in the French health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the UK indicates that some information materials designed for this purpose are inadequate, unbalanced and difficult to read. 15 However, we are not aware of equivalent research in the USA or elsewhere. Such research is particularly important in the USA where abortion is simultaneously a highly prevalent and yet highly stigmatized 16 procedure, and where there remains widespread misinformation, 17 18 poor access to services, 1 and broad variability in abortion counselling practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing emphasis on patients' experience in the health service, we believe that ensuring the quality of educational material is also important, paying attention to factors such as presentation, font size and suitability of graphics. Other specialties have assessed the quality of their leaflets, but health professionals, rather than patients, have assessed them (White et al, ; Winterbottom et al, ; Wong et al, ), often focusing on content and readability alone (Winterbottom et al, ; Wong et al, ). If the leaflet is designed for patients, then it is logical that their opinion should be sought to ensure that it addresses their questions and is presented in a user‐friendly style (Coulter, ).…”
Section: Discussionmentioning
confidence: 99%
“…The balance between content and readability is crucial. It has been suggested that inadequate attention has been paid towards the content of patient leaflets (Coulter, ) and inaccuracies or omissions have certainly been identified in leaflets (White et al, ; Winterbottom et al, ; Wong et al, ). Patients identified that our novel CVD‐RA leaflet lacked detail about what sources of information had been used to compile the leaflet, when this information had been produced and the risks associated with its advice; similar findings were observed in a review of 31 renal replacement therapy leaflets available nationwide (Winterbottom et al, ).…”
Section: Discussionmentioning
confidence: 99%